Pre- or Perinatal Arterial Ischemic Stroke - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2001)
Risk factors, coagulation profiles, and outcomes in 22 children with presumed perinatal infarct were studied at The Hospital for Sick Children, Toronto, and Chedoke McMaster Hospital, Hamilton, both participants in the Canadian Pediatric Ischemic Stroke Registry.